A Multi-Input Single-Ended Primary Inductor Converter (SEPIC): Performance Analysis for Hybrid Sources of Renewable Energy - Nayeem Ahmed; Afrid U. Araf; Sheikh M. A. Rakeen (Majlesi Journal of Electrical Engineering, 2024)
This paper focuses on the hybridization of two renewable energy sources (i.e., PV Panel and Bi-Cycle Dynamo) and the use of a Multi-Input SEPIC converter for highly efficient output from them. This paper has also presented the comparative assessment between the conventional Single-Input Single Output SEPIC (Single Ended Primary Inductor Converter) and Multi-Input SEPIC converter based on performance analysis. Both the Multi-Input SEPIC that is designed in this literature powered by the hybrid architecture of power sources and the Single-Input SEPIC are run in boost mode. The project is mainly developed with a view to facilitating the isolated rural islands and regions detached from the on-grid connections. The findings and assessments of this study are corroborated by the MATLAB/Simulink simulation results and optimally designed prototype built for miniature applications. The Multi-Input SEPIC topology has been developed in such a way that it is functional with an input voltage of 12.1V exactly and gives an output voltage of DC 53V approximately at the output terminal. To get the maximum voltage at the output from the designed circuit, the duty cycle of the converter recorded is almost 81.49%. The renewable energy sources (RES) that are used to build the prototype are Photovoltaic Panel and Bi-Cycle Dynamo. Due to the limitations of the PV Panels to generate power during the night and gloomy weather, the Bi-Cycle dynamo works as the backup power source. In performing the hardware and software analyses, various intermittent situations, solar irradiation, seasonal change, day-night phase, and other parameters are taken into consideration on the input terminal of the converter. An efficiency of 91.6% is obtained from the proposed hardware field-test analysis.